Alternative Development Concepts and Their Political Embedding: The Case of Sufficiency Economy in Thailand. Issue 3 (2nd September 2018) - Schaffar, Wolfram
Abstract: Sufficiency Economy is a local Thai alternative development paradigm, which has been enshrined in the Thai constitutions since 2006 and plays a central role in Thai political discourse since the Asian Crisis in 1997. However, the conflict between different visions of development was drawn into an intra-elite struggle, in the course of which formerly emancipatory development alternatives were co-opted into a highly authoritarian project. Today, it serves as one of the ideological foundations of the military regime, which came to power in a coup d'état in 2014. The character of this regime, however, goes beyond what Ziai (2004) calls 'enlightened authoritarianism'. It is reminiscent of fascist regimes in Europe in the 1930s. Rather than treating the concept of Sufficiency Economy as such as an authoritarian or suppressive concept, it will be argued that the authoritarian character is a result of a three-step process of politicisation which has unfolded during the last two decades.